New records of Munidopsis (Crustacea: Anomura: Galatheidae) from New Zealand with description of two new species from a seamount and underwater canyon - Schnabel, Kareen E.; Bruce, Niel L. (Zenodo, 2006)
Schnabel, Kareen E., Bruce, Niel L. (2006): New records of Munidopsis (Crustacea: Anomura: Galatheidae) from New Zealand with description of two new species from a seamount and underwater canyon. Zootaxa 1172: 49-67, DOI: 10.5281/zenodo.2645699 : {"references": ["Ahyong, S.T. & Poore, G.C.B. (2004) Deep-water Galatheidae (Crustacea: Decapoda: Anomura) from southern and eastern Australia. Zootaxa, 472, 1-76.", "Alcock, A. & Anderson, A.R.S. (1899) Natural history notes from H.M. Royal Indian marine survey ship \"Investigator\", commander T.H. Heming, R.N., commanding.-Series III, No. 2. An account of the deep-sea Crustacea dredged during the surveying season of 1897-98. Annals and Magazine of Natural History, 7(3), 1-27.", "Baba, K. (1974) Four new species of Galatheidean Crustacea from New Zealand waters. Journal of the Royal Society of New Zealand, 4(4), 381-393.", "Baba, K. (1994) Deep-sea galatheid crustaceans (Anomura: Galatheidae) collected by the 'Cidaris I' expedition off Central Queensland, Australia. Memoirs of the Queensland Museum, 35(1), 1-21.", "Baba, K. (1995) A new squat lobster (Decapoda: Anomura: Galatheidae) from an active thermal vent in the North Fiji Basin, SW Pacific. Crustacean Research, 24, 188-193.", "Baba, K. (2001) Redescription of two anomuran crustaceans, Uroptychus japonicus Ortmann, 1892 (Chirostylidae) and Munidopsis taurulus Ortmann, 1892 (Galatheidae), based upon the type material. Crustacean Research, 30, 147-153.", "Baba, K. (2005) Deep-sea chirostylid and galatheid crustaceans (Decapoda: Anomura) from the Indo-Pacific, with a list of species. Galathea Report, 20, 317 pp.", "Baba, K. & de Saint Laurent, M. (1992) Chirostylid and galatheid crustaceans (Decapoda: Anomura) from active thermal vent areas in the southwest Pacific. Scientia Marina, 56(4), 321-332.", "Baba, K. & Poore, G.C.B. (2002) Munidopsis (Decapoda, Anomura) from south-eastern Australia. Crustaceana, 75 (Special issue 3-4), 231-252.", "Borradaile, L.A. (1916) Crustacea, Part 1.-Decapoda. In: British Antarctic (\"Terra Nova\") Expedition, 1910. Natural History Reports. Zoology, Vol. 3. Arthropoda. British Museum, London, 110 pp.", "Chevaldonne, P. & Olu, K. (1996) Occurrence of anomuran crabs (Crustacea: Decapoda) in hydrothermal vent and cold-seep communities: a review. Proceedings of the Biological Society of Washington, 109(2), 286-298.", "Dallwitz, M.J., Paine, T.A. & Zurcher, E.J. (1997) User's guide to the DELTA system. A general system for processing taxonomic descriptions. 4.08, CSIRO Division of Entomology, Canberra, 160 pp.", "Doflein, F. & Balss, H. (1913) Die Galatheiden der Deutschen Tiefsee-Expedition. Wissenschaftliche Ergebnisse der Deutschen Tiefsee-Expedition auf dem Dampfer \"Valdivia\": 1898-1899, Jena, 20, 125-184, pls 12-17.", "Filhol, H. (1885) La vie au fond des mers. Les explorations sous-marines et les voyages du Travailleur et du Talisman. Masson ed. Paris, 303 pp.", "Goffredi, S.K., Paull, C.K., Fulton-Bennett, K., Hurtado, L.A. & Vrijenhoek, R.C. (2004) Unusual benthic fauna associated with a whale fall in Monterey Canyon, California. Deep-Sea Research I, 51, 1295-1306.", "Henderson, J.R. (1885) Diagnoses of the new species of Galatheidae collected during the 'Challenger' Expedition. Annals and Magazine of Natural History, series 5, 16, 407-421.", "Henderson, J.R. (1888) Report on the Anomura collected by H.M.S. Challenger during the years 1873-76. Report on the scientific results of the voyage of H.M.S. Challenger during the years 1873-76, Zoology, 27, 221 pp, 21 pls.", "Khodkina, I.V. (1981) A contribution to the fauna of the family Galatheidae (Decapoda) of the south-west Pacific. Zoologicheskii Zhurnal, 60, 1261-1264 (in Russian with English summary).", "Koelbel, K. (1892) Beitrage zur Kenntnis der Crustaceen der Canarischen Inseln. Annalen des naturhistorischen Hofmuseums, Wien, 3, 109, pl. x., figs. 3-16.", "MacGilchrist, A.C. (1905) Natural history notes from the R.I.M.S. 'Investigator', Capt. T.H. Heming, R.N. (retired), commanding.-Series III., No. 6. An account of the new and some of the rarer decapod Crustacea obtained during the surveying seasons 1901-1904. The Annals and Magazine of Natural History, 7(15), 233-268.", "Macpherson, E. & Segonzac, M. (2005) Species of the genus Munidopsis (Crustacea, Decapoda, Galatheidae) from the deep Atlantic Ocean, including cold-seep and hydrothermal vent areas. Zootaxa, 1095, 1-60.", "Martin, J.W. & Haney, T.A. (2005) Decapod crustaceans from hydrothermal vents and cold seeps: a review through 2005. Zoological Journal of the Linnean Society, 145, 445-522.", "Ortmann, A. (1892) Die Decapoden-Krebse des Strassburger Museums IV. Die Abteilungen Galatheidea und Paguridea. Zoologische Jahrbucher, Abteilung fur Systematik, Geographie un Biologie der Tiere, 6, 241-326, pls. 11, 12.", "Samouelle, G. (1819) The entomologist's useful compendium; or an introduction to the knowledge of British insects. Thomas Boys, London, 496 pp.", "Thomson, G.M. (1899) Revision of the Crustacea Anomura of New Zealand. Transactions and Proceedings of the New Zealand Institute, 31, 169-197, pls. 20, 21.", "Tunnicliffe, V., McArthur, A. & McHugh, D. (1998) A biogeographical perspective of the deep-sea hydrothermal vent fauna. Advances in Marine Biology, 34, 353-442.", "Vereshchaka, A.L. (2005) New species of Galatheidae (Crustacea: Anomura: Galatheoidea) from volcanic seamounts off northern New Zealand. Journal of Marine Biology Association U.K., 85, 137-142.", "Whiteaves, J.F. (1874) On recent deep-sea dredging operations in the Gulf of St. Lawrence. American Journal of Science, 7, 210-279.", "Williams, A.B. & Turner, R.D. (1986) Squat lobsters (Galatheidae: Munidopsis) associated with mesh-enclosed wood panels submerged in the deep sea. Journal of Crustacean Biology, 6(3), 617-624.", "Wright, I.C., Worthington, T.J. & Gamble, J.A. (2006) New multibeam mapping and geochemistry of the 30\u00ba-35\u00ba S sector, and overview, of the southern Kermadec arc volcanism. Journal of Volcanology and Geothermal Research, 149, 263-296."]}